A89: The Relationship Between Benign Joint Hypermobility Syndrome and Developmental Coordination Disorders in Children. Issue Volume 66:Issue(2014)supplement 3 (March 2014) - Easton, Victoria; Bale, Peter; Bacon, Holly; Jerman, Emma; Armon, Kate; Macgregor, Alex J
Abstract : Background/Purpose: Benign joint hypermobility syndrome (BJHS) is a heritable connective tissue disorder, which is characterised by excessive joint flexibility and musculoskeletal dysfunction. In childhood, BJHS has been linked clinically with disorders of motor control, however the association remains poorly characterised and the extent to which this reflects developmental variation remains uncertain. A systematic review found reduced lower limb joint proprioception in those with BJHS compared with non‐hypermobile cohorts with possible implications on co‐ordination. The purpose of this study was to examine baseline data from an interventional study of BJHS in childhood to assess the relationship between joint hypermobility and motor control. Methods: The study subjects included 119 children between the ages of 5 and 16 years. All had documented joint hypermobility (assessed by a paediatric rheumatologist) and musculoskeletal pain or dysfunction. Motor ability was assessed using the norm‐referenced Movement Assessment Battery for Children 2 (M‐ABC 2); a validated tool that identifies developmental coordination disorder. The assessment covers three domains: 1. Manual Dexterity 2. Ball Skills /throwing catching skills 3. Static and Dynamic Balance. The test contains eight activities for three age groups: 3–6 years; 7–10 years and 11–16 years. Total standard scores and percentiles were calculated using a standard scoring system. Children with age‐corrected scores falling below the 15th percentile were defined as having movement difficulty. Those that score below 5 th Centile were classified as having significant movement difficulty. The child's functioning, including pain and wellbeing was assessed using the Childhood Health Assessment Questionnaire (CHAQ) which is a validated parent questionnaire for the use in children with juvenile idiopathic arthritis but was modified for use in this study. Results: Among the children with BJHS that were assessed, 32.8% scored ≤15 percentile on the M‐ABC (p<0.001). 18.4% scored less than or equal to 5% on the M‐ABC, suggesting they have significant movement difficulty. Movement difficulty was commoner in males (40%) than females (25%). The prevalence of movement difficulty was higher in younger subjects when compared with older children with BJHS (5 to 8 years = 41%; 9 to 12 years: 29%; 13 to 16: 19%). There was no correlation between degree of hypermobility and level of pain. The CHAQ score showed a moderate inverse correlation to the level of motor difficulty (r = −0.4186, R‐squared = 0.175, p < 0.01). Conclusion: Movement difficulty is a common independent component of BJHS in childhood. An evaluation of motor function needs to be included as part of the assessment of all children with BJHS and may merit targeted intervention as its presence represents a lower quality of functioning. Further research is needed into children with BJHS and movement difficulty, who may benefit from targeted interventions.